Penerapan Metode TOPSIS dan Profile Matching Sistem Pendukung Keputusan Seleksi Siswa Peserta LKS - Dita Indah Pratama Putri; M. Fakhriza; Muhammad Dedi Irawan (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
In determining which students will take part in the Student Competency Competition (LKS), it is necessary to pay attention when determining the selection results for LKS participants. The Student Competency Competition is an annual competency between students at the vocational school level according to the skills taught at the vocational school. So far, the process of selecting students who will participate in the LKS has only been done manually by selecting students who are active enough in learning so that only those students will take part in the LKS. The aim of this research is to design and build a decision support information system using the TOPSIS (Technique for Order Preference by Similiarity to Ideal Solution) method and web-based Profile Matching which can make it easier for teachers to select students who will take quality and fulfilling LKS. Assessment standards in the field of competence. The system development method used in this research is the Rapid Application Development (RAD) method. With this information system, it is hoped that it can help teachers in selecting students who will take the LKS. From the preference values, it can be concluded that the alternative (third row) has the most optimal weight value compared to the other alternative values. Therefore, it can be seen that (third row) are students who have the right or are eligible to become prospective participants in vocational school level LKS who pass the first selection with a preference value (0.881).